Optimization methods for manufacturing - Leondes, Cornelius T.; CRC Press (Boca Raton : CRC Press, 2001)
In the competitive business arena companies must continually strive to create new and better products faster, more efficiently, and more cost effectively than their competitors to gain and keep the competitive advantage. Computer-aided design (CAD), computer-aided engineering (CAE), and computer-aided manufacturing (CAM) are now the industry standa
Chapter 1 Synchronization of Production Rate with Demand Rate in Manufacturing Systems -- chapter 2 Integrated Product and Process Management for Engineering Design in Manufacturing Systems -- chapter 3 Project Selection Problems for Production-Inventory-Distribution Scheduling in Manufacturing Plants -- chapter 4 Computer-Aided and Integrated Manufacturing Systems -- chapter 5 Job-Shop Scheduling for Manufacturing with Random Time Operations -- chapter 6 Failure Diagnosis in Computer-Controlled Systems -- chapter 7 Analysis of Stochastic Models in Manufacturing Systems Pertaining to Repair Machine Failure -- chapter 8 Petri Net Modeling and Scheduling of Automated Manufacturing Systems -- chapter 9 Improvement of Damping Characteristics in Machine Tools in Manufacturing Systems.
OCLC-licensed vendor bibliographic record.
Keywords: Mathematical optimization; Production planning; Manufacturing processes; CAD/CAM systems; TECHNOLOGY & ENGINEERING / Industrial Engineering; TECHNOLOGY & ENGINEERING / Industrial Technology; TECHNOLOGY & ENGINEERING / Manufacturing; TECHNOLOGY & ENGINEERING / Technical & Manufacturing Industries & Trades; COMPUTERS / General; TECHNOLOGY / Engineering / Industrial